2018
DOI: 10.1080/2162402x.2018.1457598
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine levels in breast cancer patients during neoadjuvant treatment with bevacizumab

Abstract: A high concentration of circulating vascular endothelial growth factor (VEGF) in cancer patients is associated with an aggressive tumor phenotype. Here, serum levels of 27 cytokines and blood cell counts were assessed in breast cancer patients receiving neoadjuvant chemotherapy with or without bevacizumab (Bev) in a randomized cohort of 132 patients with non-metastatic HER2-negative tumors. Cytokine levels were determined prior to treatment and at various time-points. The cytotoxic chemotherapy regimen of fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 64 publications
5
25
0
1
Order By: Relevance
“…We found that most of the significant changes occurred between screening and 12 weeks. We interpret this as a result of the potent effects of chemotherapy locally at the tumor site but also systemically as we previously reported …”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…We found that most of the significant changes occurred between screening and 12 weeks. We interpret this as a result of the potent effects of chemotherapy locally at the tumor site but also systemically as we previously reported …”
Section: Resultssupporting
confidence: 83%
“…a – e ) with significantly different levels according to treatment arm (ANOVA FDR corrected p ‐value <0.05; Supplementary Table S3). We previously described a Bev‐induced significant decrease in VEGF‐A levels accompanied by a decrease in IL‐12 and IP‐10 . Here, we show that levels of ALCAM and AXL followed a similar pattern with marked decrease in serum levels induced by Bev (Figs.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations